ANALISIS PERILAKU KONSUMTIF PADA WANITA KARIER DI KELURAHAN BANSIR DARAT PONTIANAK - Nurfitrianti, Nurfitrianti; Asriati, Nuraini; Ramadhan, Iwan (Universitas Tanjungpura, 2024)
The purpose of this study was to determie the consumptive behavior of career women in Bansir Darat, Pontianak. The approach used in this research is a qualitative approach with descriptive research methods. Data collection techniques used are observation, interview, and documentation techniques. The results show that career women have free time and time for family when they are off work. Career women who carry out duties as housewives have higher levels of consumptive behavior after marriage. Impulsive behavior in career women in Bansir Darat, Pontianak is consumptive behavior based on a sudden emotional urge to buy an item without seeing the benefits and value of the item that has been purchased. Wasteful consumptive behavior among career women in Bansir Darat, Pontianak is consumptive behavior that spends money without clarity. Consumptive behavior seeking pleasure in career women in Kelurahan Bansir Darat, Pontianak is consumptive behavior that reflects a luxurious and glamorous life.